Mean Exercise Duration And Fine Motor Speed In Elderly Living In Bhakti Luhur Tropodo Orphange And Nursing Home - Suhardi, Maria A; Kurniawati, Nita; Konginan, Agustina (JOURNAL OF WIDYA MEDIKA JUNIOR, 2020)
Introduction: For the elderly to live independently and productively, good fine motor skill is needed. It is well known that exercise can preserve fine motor skills. Still, the effect of practices in Bhakti Luhur Orphanage and Nursing Home: Oma-oma’s gym and tai chi haven’t been explored before. Aim: The goal of this research is to analyze the correlation between the median of the exercise duration and fine motor skills represented by the average of finger tapping test on trial three to trial five. Methods: This cross-sectional research employed purposive sampling yielding 22 elderly (≥60 years old) who understood the order given, agreed to join the research, and also free from motor impairment due to cerebrovascular accidents, parkinsonism, pain or arthritis on the dominant hand, and nil from psychiatric drugs as samples. Result: There was a slight correlation between the two variables, which is insignificant (r=0,341, p=0,120) between the duration of the exercises and motor speed. Conclusion: There is no significant correlation between exercise duration and fine motor skills in the elderly in Bhakti Luhur Orphanage and Nursing Home.